Effect of Some Antifoam Agents and Oxygen Transfer Rate on Citric Acid Production by Submerged Fermentation - Kamal, K.P.; Verma, U.N.; Nag, A.K.; Singh, S.P. (Asian Journal of Chemistry, 2010)
The effect of antifoam agents, viz., octadecanol, groundnut oil and silicone oil and oxygen transfer rate (OTR) has been studied on citric acid yield by A. niger under submerged fermentation. It has been observed that groundnut oil gave the maximum yield of citirc acid in comparison to octadecanol and silicone oil. So far as the OTR is concerned a volume of 100 mL of the medium per one litre flask is optimum for the production of citric acid.